Hüttl Tivadar (1884-1955) Debrecen klinikaalapító és iskolateremtő sebész professzora - Balázs, György; Péterffy, Árpád (Gerundium, 2015)
HÜTTL TIVADAR (1884–1955), PROFESSOR SURGEON, FOUNDER OF A SCHOOL AND CLINIC IN DEBRECEN. After inishing his studies, Tivadar Hüttl worked in the Institute of Pathology at the Budapest University besides Professor Antal Genersich, later int he Clinic of Surgery besides Professor Tibor Verebély. From 1921 he worked as Deputy director of the forming Faculty of Medicine at the Tisza István University in Debrecen, in 1922 he was appointed as the full professor of Surgery and the Director of the Clinic of Surgery. During his leadership he established several departments which became clinics later on. He created a truly scientiic school environment, professors, hospital directors became his students. In the academic year of 1930–40 he was the Rector of the university. He was wrongfully accused in 1945 and he was divested of his professor title. Later he worked as the head physician of the State Institute of Oncology.